Handled RF spectrum analyser using Arduino - Soares, Vitor Miguel Melo (2014)
Radio frequency term refers to the electromagnetic spectrum bandwidth used to transmission of electromagnetic signals trough free space. The human knowledge about this phenomena turns possible to set wireless communications between electronic devices. The analysis of that spectrum is demanding in order to achieve proper communications between those devices. Whit spectrum analysers is possible to observe some physical characteristics of the communication. The aim of this document is to furnish information about the project, design and implementation of a spectrum analyser using open source digital control technology, Arduino.